Improving pedal power during semireclined leg cycling. - Trumbower, R.D.
Using time-sequence analysis of EMG measurements to determine if changes in muscle activation timing, sequencing, and stimulation can improve pedaling effectiveness.
Keywords: EMG measurements; Muscle activation timing; Muscle stimulation; Pedal power; Semireclined leg cycling; Time-sequence analysis